Cultural Mapping - A Developmental Tool for Enhancing the Destination’s Image. Case Study of Cuttack - MOHANTY, Shruti; MISHRA, Sitikantha; MOHANTY, Sasmita (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.v10.1(33).05, 2019)
Tourism is one of the major contributors of the global economy, which helps in generating millions of jobs and billions of dollars worldwide. In emerging countries it is considered as the only tool for development and by many communities it is the only chance for increasing the quality of life. If one looks from the socio-cultural perspective, tourism is the source that brings together people from different cultures and traditions with different background. Cultural mapping is a developmental tool that makes use of practical and participatory planning which is an emerging mode of research. Cultural mapping also makes use of the theory of “Making the Intangibles Visible”. Odisha has been the tourist’s paradise as it is a home to many historical and religious places. It is also culturally enriched in many ways, but the fact that it still lags behind cannot be hidden, when compared to other destinations in the world despite the richness in every aspect. Cuttack is a district in eastern Odisha which has a history of 1000 years, known as the Millennium City as well as the Silver City which can be the best example where Cultural Mapping can be used to enhance the image of the destination. The data collection method used in the study is questionnaire method with a sample of 100 respondents is taken by applying random sampling technique. The objective of the study is to find out the areas where Cuttack’s image as cultural city can be established through the innovative tool of cultural mapping. The result of this research showed that few factors are indicative that can be used in the cultural mapping thereby enhancing the destination’s image.